KINERJA DINAS PEMADAM KEBAKARAN DAN PENYELAMATAN KOTA PEKANBARU - Rahmadani, Suci Fitri; Sadad, Abdul (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
The performance of the Pekanbaru City Fire and Resue Service in impro the capital of Riau Province and a center of trade. Therefore, Pekanbaru City is growing and its development progress is getting faster every year. With the rapid development of Pekanbaru City, the risk of fire is increasing. The population of Pekanbaru City is getting denser, buildings are being built more and more, industry is growing so that there is a danger of fire and if a fire occurs it needs special handling. The Pekanbaru City Fire and Rescue Service as an implementing element of the Regional Government has a main task in carrying out regional government affairs in the field of fire and disaster management based on the principles of autonomy and assistance tasks. The research was conducted based on problems that occurred in the implementation of fire and rescue disaster management carried out by the Pekanbaru City Fire and Rescue Service. The purpose of this study was to analyze the performance of the Pekanbaru City Fire and Rescue Service and identify factors that hinder performance. The research method used is descriptive qualitative with data collection techniques, namely interviews, observation and documentation. Performance appraisal based on Dwiyanto's theory, namely productivity, service quality, responsiveness, responsibility and accountability. Factors that hinder performance are human resources, facilities and infrastructure and budget. Based on research, the performance of the Pekanbaru City Fire and Rescue Service is still not running optimally, targets are not fulfilled, officers are late in providing services to the community, insufficient budget allocations, and inadequate facilities and infrastructure exist so that it can be concluded that the performance of the Fire Department and Rescue of Pekanbaru City has not gone well. Keyword : Perfomance, Fire and Rescue Department, Public Department